COULD YOUTUBE BENEFIT SECONDARY EDUCATION’S ELT? - Anselmus Inharjanto; Ega Leovani (ELTR Journal, 2022)
YouTube is definitely a digital platform that seems to be one of the most-used search engines nowadays. It offers an endless supply of authentic, real-life, up-to-date materials that may benefit English Language Teaching (ELT). This research aims to investigate to what extent the authentic materials through YouTube may benefit English Language Teaching of secondary education in Indonesia. This descriptive qualitative study employed questionnaires, classroom observations and textbook analysis as the data collection methods. A purposive sample of 125 XI graders of senior high school participated in this study. This primary research was followed by secondary one by reviewing recent literary works systematically. The results of the study suggest that Indonesian students seemingly need more exposure to English language and the advance of information and communication technologies (ICTs), particularly YouTube, is likely to foster English Language Teaching of secondary education in Indonesia since it provides abundant authentic materials related to real-life contexts.